Ruxolitinib inhibits cytokine production by human lung macrophages without impairing phagocytic ability - Mantov, Nikola; Zrounba, Mathilde; Brollo, Marion; Grassin-Delyle, S; Glorion, Matthieu; David, Mélanie; Naline, Emmanuel; Devillier, Philippe; Salvator, Hélène (Frontiers in Pharmacology, 2022)
Background The Janus kinase (JAK)1/2 inhibitor ruxolitinib has been approved in an indication of myelofibrosis and is a candidate for the treatment of a number of inflammatory or autoimmune diseases. We assessed the effects of ruxolitinib on lipopolysaccharide (LPS)- and poly(I:C)-induced cytokine production by human lung macrophages (LMs) and on the LMs’ phagocytic activity. Methods Human LMs were isolated from patients operated on for lung carcinoma. The LMs were cultured with ruxolitinib (0.5x10-7 M to 10-5 M) or budesonide (10-11 to 10-8 M) and then stimulated with LPS (10 ng.mL-1) or poly(I:C) (10 µg.mL-1) for 24 h. Cytokines released by the LMs into the supernatants were measured using ELISAs. The phagocytosis of labelled bioparticles was assessed using flow cytometry. Results Ruxolitinib inhibited both the LPS- and poly(I:C)-stimulated production of tumor necrosis factor alpha, interleukin (IL)-6, IL-10, chemokines CCL2 and CXCL10 in a concentration-dependent manner. Ruxolitinib also inhibited the poly(I:C)- induced (but not the LPS-induced) production of IL-1ß. Budesonide inhibited cytokine production more strongly than ruxolitinib but failed to mitigate the production of CXCL10. The LMs’ phagocytic activity was not impaired by the highest tested concentration (10-5 M) of ruxolitinib. Conclusion Clinically relevant concentrations of ruxolitinib inhibited the LPS- and poly(I:C)-stimulated production of cytokines by human LMs but did not impair their phagocytic activity. Overall, ruxolitinib’s anti-inflammatory activities are less intense than (but somewhat different from) those of budesonide – particularly with regard to the production of the corticosteroid-resistant chemokine CXCL-10. Our results indicate that treatment with a JAK inhibitor might be a valuable anti-inflammatory strategy in chronic obstructive pulmonary disease, Th1-high asthma, and both viral and nonviral acute respiratory distress syndromes (including coronavirus disease 2019).